2019
DOI: 10.1021/acssuschemeng.8b05374
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free One-Step Synthesis of g-C3N4 Nanosheets with Simultaneous Porous Network and S-Doping for Remarkable Visible-Light-Driven Hydrogen Evolution

Abstract: Graphitic carbon nitride (g-C 3 N 4 ) has been widely studied as a fascinating visible-light-response two-dimensional semiconductor photocatalyst. Nevertheless, the quantum yield of g-C 3 N 4 is unsatisfactory due to the insufficient surface reactive sites and slow charge migration efficiency caused by grievous agglomeration and large grain size. Herein this obstacle is overcome through a facile eco-friendly strategy based on effects from a bubble template and nonmetal heteroatom doping of g-C 3 N 4 . This tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(54 citation statements)
references
References 49 publications
0
50
0
Order By: Relevance
“…All of the FT-IR spectra clearly exhibited similar peaks that can be attributed to the typical chemical bonds of pure g-C 3 N 4. The strong peak at 810 cm –1 can be assigned to the breathing mode of triazine units, , whereas the absorption bands in the region of 1200–1700 cm –1 can be ascribed to the typical stretching modes of aromatic CN and CN in tri-s-triazine rings. , The broad peaks in the range of 3000–3600 cm –1 corresponding to the NH stretching vibrations or structural OH groups of the Pt/AO and Pt/NO samples underwent a blue shift and a notable increase in band intensity in comparison with those of Pt/AB and Pt/NB, indicating that additional OH functional groups were generated over the g-C 3 N 4 surface after the chemical oxidation treatment. This is later confirmed using the XPS data.…”
Section: Resultsmentioning
confidence: 99%
“…All of the FT-IR spectra clearly exhibited similar peaks that can be attributed to the typical chemical bonds of pure g-C 3 N 4. The strong peak at 810 cm –1 can be assigned to the breathing mode of triazine units, , whereas the absorption bands in the region of 1200–1700 cm –1 can be ascribed to the typical stretching modes of aromatic CN and CN in tri-s-triazine rings. , The broad peaks in the range of 3000–3600 cm –1 corresponding to the NH stretching vibrations or structural OH groups of the Pt/AO and Pt/NO samples underwent a blue shift and a notable increase in band intensity in comparison with those of Pt/AB and Pt/NB, indicating that additional OH functional groups were generated over the g-C 3 N 4 surface after the chemical oxidation treatment. This is later confirmed using the XPS data.…”
Section: Resultsmentioning
confidence: 99%
“…9 Zhou et al reported a porous g-C 3 N 4 nanosheet with a hydrogen production rate 5.3 times higher than that of bulk g-C 3 N 4 , owing to the more effective charge carrier separation capacity and larger specific surface area. 10 Introduction of nitrogen defects into g-C 3 N 4 catalysts for superior photocatalytic activity has attracted extensive attention recently. 11−13 For example, Han et al reported a defect-rich amorphous g-C 3 N 4 and demonstrated that nitrogen vacancies result in a narrowed band gap, extended visible-light absorption, and quenched radiative recombination for H 2 evolution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among various 2D based substrates, 2D g‐C 3 N 4 , as a desirable option to accommodate the heteroatom dopants by virtue of its stable phase, nontoxicity and low‐cost, has been closely connected with the defect engineering of 2D photocatalysts through heteroatom doping. [ 66 ]…”
Section: Defect Engineeringmentioning
confidence: 99%